The effect of personal selling and relationship marketing on customer loyalty and satisfaction as an intervening variable in PT. Welty Indah Perkasa Palembang Branch - Roby Yansah; Ahmad Maulana; Muchsin Saggaf Shihab (Goodwood Publishing, 2025)
Purpose: This study aimed to examine the effects of personal selling and relationship marketing on customer satisfaction and loyalty at the PT Welty Indah Perkasa Palembang branch. Methodology: The study population comprised 302 customers of PT Welty Indah Perkasa Palembang branch who made purchase transactions during 2023, while the sample included customers with regular monthly transactions from January 1 to December 31, 2023. Data were analyzed using multivariate analysis with a structural equation modeling (SEM) program. Results: The analysis shows that personal selling and relationship marketing influence both customer satisfaction and loyalty, with customer satisfaction strengthening the effect on loyalty. Personal selling has the strongest impact on satisfaction, whereas relationship marketing has the weakest impact on loyalty. Conclusion: Effective personal selling and relationship marketing strategies play a critical role in enhancing customer satisfaction, which, in turn, fosters greater customer loyalty. Among these factors, personal selling emerged as the most impactful driver of satisfaction and loyalty within the company’s customer base.Limitation: This study is limited to a single branch of PT Welty Indah Perkasa and uses a sample confined to customers with regular monthly transactions for over one year. The findings may not be fully generalizable to other branches, industries, or customers with irregular purchase patterns. Contribution: This study provides empirical evidence of the key role of personal selling and relationship marketing in fostering sustainable customer satisfaction and loyalty in the B2B context, offering strategic guidance to prioritize personal selling and enhance relationship marketing for long-term engagement.